The role of corporate governance in the relationships of family company with real earnings management - Masri, Indah (Jurnal Akuntansi, 2018)
The purpose of this research was to determine the effect of family ownership on real earnings management with corporate governance as a moderation variable in this relationship. This research is also looking at the role of accrual earnings management as a substitute in the relationship accrual earnings management with real earnings management in a family company. This study uses data 61 manufacturing companies on the Indonesia Stock Exchange in the period 2010 to 2013. The research results according to which hypothesized that family firms tend to negatively affect with real earnings management. The role of corporate governance as strengthening internal oversight negative effect on family companies with real earnings management. The results also proved the existence of a relationship of substitution for family firms tend to be doing accrual earnings management than real earnings management. This is because on the one hand the motivation of control as a strong incentive to do accrual earnings management in the family company, while on the other hand, the family companies tend to dislike real earnings management for their negative performance impact.